Genetically Predicted Fibroblast Growth Factor 23 and Major Cardiovascular Diseases, Their Risk Factors, Kidney Function, and Longevity: A Two-Sample Mendelian Randomization Study - Liang, Ying; Luo, Shan; Schooling, C. Mary; Au Yeung, Shiu Lun (Frontiers in Genetics, 2021)
Abstract Introduction Fibroblast growth factor 23 (FGF23), a potential biomarker for kidney function, is related to cardiovascular disease (CVD) and diabetes although it is unclear whether the relation is causal. This study evaluated the associations of genetically predicted FGF23 with major CVDs, their risk factors, kidney function and longevity using Mendelian randomization. Methods This is a two-sample Mendelian randomization (MR) study using summary statistics from large genome wide association studies. Primary outcomes included coronary artery disease (CAD), myocardial infarction, heart failure and atrial fibrillation. Secondary outcomes included cardiovascular risk factors, kidney function and longevity. We used 4 SNPs predicting FGF23, excluding rs2769071 in the ABO gene which likely violates the MR exclusion-restriction assumption. We used inverse-variance weighted (IVW) as the primary statistical method to assess associations of FGF23 with the outcomes. Sensitivity analyses included weighted median and MR-Egger. We repeated the analyses including all 5 SNPs. Lastly, we validated the positive findings from the main analyses in a smaller study, i.e., FinnGen. Results Using IVW, genetically predicted higher FGF23 was inversely associated with risk of CAD (odds ratio (OR): 0.69, 95% confidence interval (CI): 0.52 to 0.91) and type 2 diabetes mellitus (T2DM) (OR: 0.70, 95% CI: 0.52 to 0.96), but not with the other outcomes. The weighted median and MR-Egger estimates were directionally consistent. Conclusions This study suggests genetically predicted higher FGF23 may be protective against CAD and T2DM. Future studies should explore the underlying mechanisms related to the potential protective effect of FGF23. FGF23 was unlikely a cause of poorer renal function.